Seroprevalence of primary health care workers in Saint-Petersburg during a measles epidemic - T. M. Chemovа; V. N. Timchenko; E. V. Barakina; E. B. Pavlova; A. N. Nazarova; А. L. Balashov; I. A. Egorova; Е. L. Kostritsa; A. A. Zherebtsova (Детские инфекции (Москва))
The measles situation is still unstable — there are imported cases, the formation of nosocomial foci with the involvement of medical personnel, patients and visitors of medical institutions.Objective of the study: to assess the level of seroprevalence of primary health care workers in St. Petersburg during the period of epidemic trouble with measles.Materials and methods: An open retrospective randomized uncontrolled study of the intensity of specific immunity to measles in 980 employees aged 18 to 78 years, examined in July-September 2018, was carried out. The level of anti-measles IgG antibodies was determined by the method of enzyme-linked immunosorbent assay (810 people) and passive hemagglutination reactions (170 people). The results are presented with the indication of the shares (%) and the calculation of the 95% confidence interval according to Clopper — Pearson. Differences between groups were assessed using Pearson's chi-square test (%2). Differences in the groups were considered statistically significant when the criterion level was p < 0.05.Results: It was found that 8.2% of personnel are not protected against measles infection. At the same time, the number of seronegative persons among doctors (8.1 %), nurses (7.7%) and non-medical workers (9.6%) differed statistically. Age-related differences in the immune layer were revealed — the greatest susceptibility was observed in persons under 30 years of age (1 8.3%). Anti-measles antibodies in those who had been ill persisted for a long time and at a high level. At the same time, the intensity of post-vaccination immunity decreased over time, and 20 years after immunization, the number of seronegative individuals increased significantly. Only 64.1 % of those surveyed had two vaccinations, more than a third were immunized once. Nevertheless, the proportion of people unprotected from measles exceeded the criterion of epidemic well-being with the same frequency in both groups (9.2% and 1 0.4%, respectively).The results of a serological study showed that the presence of a record of two vaccinations in the certificate in 9.2% of cases does not guarantee protection in case of contact with a patient with measles. Only a serological examination is evidence of specific immunity to measles infection.